Intervenção comportamental para mulheres com fibromialgia e má qualidade do sono ou insônia - Kirchner, Luziane de Fátima (Universidade Federal de São Carlos, 2017)
The present thesis is described in research papers format, whose development is justified by literature review, phase of intervention tests to improve the plans of data collection and data collection itself. PROPOSAL 1 (Literature review) composes paper 1 and along with paper 2 present the synthesis of the analyzed variables, evaluation and intervention forms and the main results of cognitive-behavioral intervention studies on people with chronic pain, whose results helped in the conduction of the following studies. PROPOSAL 2 (Pilot study) presents a study aimed at women with fibromyalgia (FM) and poor sleep quality, whose research design allowed to evaluate: the effects of a brief behavioral intervention for pain and sleep combined with a relaxation training, and the isolated effect of relaxation training, both compared to the control group without intervention (paper 3) and the effect and order of application of the two components (pain and sleep management) of this intervention (paper 4). And, PROPOSAL 3 (Data collection) corresponds to the study conducted to women with FM and insomnia, from Multiple Baseline Design with withdrawal of the intervention and pre and post test evaluations, which was split in two articles: one of them evaluated the effect of two components of a behavioral intervention for pain management (1 - management of the physical environment conditions and 2 - interpersonal relationship management), on pain and sleep indicators (paper 5), and the other evaluated the effect of this intervention on other health indicators, besides clinical significance and reliable change (paper 6). Direct self-report and self-registration measures for pain and/or sleep assessment were considered in all intervention studies. Data showed that the brief analytical-behavioral intervention (pilot study) for pain and sleep had an impact on reducing the intensity and incapacity of pain and anxiety, and the intervention for pain (data collection itself) had an impact both on pain and sleep, anxiety, depression, stress and social skills self-reported indicators. Considering the direct measures, both studies (pilot and data collection) showed a change in the sleep pattern (mainly sleep latency) evaluated by actigraphy, but there was no change in the Cortisol Awakening Response (CAR). The present study results are in line with the literature, and methodological aspects were discussed.
Behavioral intervention for women with fibromyalgia and poor sleep quality or insomnia
Keywords: Fibromialgia; Qualidade do sono; Insônia; Intervenção comportamental; Fibromyalgia; Sleep quality; Insomnia; Behavioral intervention; CIENCIAS HUMANAS::PSICOLOGIA